Internet of Things-Based Automatic Trash Can Prototype Using Arduino Mega 2560 - Sumarno Wijaya; Ahmad Fatoni Dwi Putra; Yuan Sa'adati; Hadi San, Ahmad Syahrul; Yunus, Muhajir; Talirongan, Florence Jean B.; G. Tangaro, Diana May Glaiza; Grancho, Bernadine (Indonesian Journal of Modern Science and Technology, 2025)
The development of Internet of Things (IoT) technology encourages the creation of various smart device innovations that can be applied in everyday life, one of which is an automatic waste management system. This research aims to design and implement an IoT-based automatic trash can prototype using an Arduino Mega 2560 microcontroller that is able to detect the presence of people who will throw away garbage, open and close the lid of the tub automatically, and provide notification if the trash can is full. This research uses an experimental method by combining ultrasonic sensors, servo motors, and LED indicators as the main components. The test results show that the device works well and in accordance with the researcher's expectations. Ultrasonic sensor 1 can detect the presence of objects in front of the trash can and trigger the servo motor to open and close the lid automatically. Ultrasonic sensors 2 and 3 are also able to detect the height of the garbage and activate the servo motor while the indicator LEDs also function as designed: LED 1 blinks when someone approaches to take out the trash, while LED 2 and LED 3 light up when the sensors detect that the trash has reached a certain height limit. In addition, the system is energy efficient as it only activates when an object is detected, making it suitable for households and educational institutions.